Evaluating measurements of workers demographic and psychometric profile: a prelude to sustainable development of behavioural safety in Sarawaks oil & gas construction industry - Lai, Hon-Kuan; Adam, Nor Mariah; Adam Assim, Mohamad Ibrani Shahrimin; Mat Jusoh, Nurul Hidayu; Marzuki, Omar Faruqi (Human Resource Management Academic Research Society, 2023)
Significant accidents in Sarawaks oil and gas construction sites often involve fatality, presumably behavioural related, attracting substantial unwarranted attention from the press. Therefore, it is imperative to develop a measuring instrument to identify and gauge workers demographic and psychometric attributes that may significantly influence workers safe behaviour potentials to reduce the risk of occupational accident hazards in a sustainable manner. Thus, this paper evaluates constructs validity and reliability, and statements communality of this new instrument to confirm its objectivity and clarity in measuring constructs as intended. A 5-point Likert-type scaled instrument consists of 93 initial statements was created and utilized to evaluate 51 oil and gas construction workers, randomly selected from local-based oil and gas construction service providers. Demographic results indicate most respondents have more than 5 years work experience, with a high level of experiences in occupational accidents, and almost all respondents possessed some kinds of knowledge and experience in accident prevention to different extents. The analysis also found that most demographic and psychometrics statements of initial research framework yielded a high reliability (Cronbachs Alpha > 0.7). High validity (KMO 0.6) except items BPV3 and LSM5 with valid dispensations. High communality value indicates that the extracted constructs represent the variables well. Through confirming the validity and reliability of initial research framework, and removal of statements with lower communality, a statistically valid and reliable multi-lingual questionnaires is therefore synthesized for subsequent research.